The reverse buffering effects of social support on the relationships between stresses and mental health: a survey of Chinese adults during the COVID-19 lockdown - Chengbin Liu; Ning Huang; Farooq Ahmed; Muhammad Shahid; Xiaohua Wang; Jing Guo (European Journal of Psychotraumatology, 2021)
Background: People lived through different types of stresses during the COVID-19 pandemic, and stresses from different sources are believed to associate differently with mental health. Objectives: The current study aims to examine the relationship between types of stresses and mental health among the general Chinese adult population, and further explore the moderating role of social support in these relationships. Methods: This study was conducted from 1 to 10 February 2020, and 2441 participants were recruited through an online cross-sectional survey from 31 provinces in China. We used multiple linear regression analyses to examine the associations among stresses’ types, social support, and mental health. Results: The study revealed that all types of stresses were associated with more mental health symptoms. Stresses from lockdown policy presented stronger associations with mental health symptoms (Beta = 0.387 for depressive symptoms and Beta = 0.385 for post-traumatic stress symptoms (PTSS)) than stresses from pandemic fear (Beta = 0.195 for depressive symptoms and Beta = 0.221 for PTSS). Moreover, greater social support enhanced the positive associations between stresses and mental health symptoms. Conclusions: Stresses from lockdown policies during the early stage of the COVID-19 epidemic are worthy of more attention. We urge more interventions are required to reduce the side-effect of lockdown policies, and also discuss implications for mental health promotion.